Reputation: 7927
I have the below code that generates LambdaExpression
at run time based on my SearchTerm
inputs. I'm trying to build a dynamic where
clause. However I'm stuck at how to convert from LambdaExpression
to Expression<Func<T,bool>>
private static Expression<Func<T,bool>> GetSearchAppliedQuery(IEnumerable<SearchTerm> terms)
{
var parameterExpression = ExpressionHelper.Parameter<T>();
Expression finalExpression = Expression.Constant(true);
Expression subExpression = Expression.Constant(false);
// Build up the LINQ Expression backwards:
// query = query.Where(x => x.Property == "Value" && (x.AnotherProperty == "Value" || x.SomeAnotherProperty == "Value"));
foreach (var term in terms)
{
var hasMultipleTerms = term.EntityName?.Contains(',') ?? false;
if (hasMultipleTerms)
{
var entityTerms = term.EntityName.Split(',');
foreach (var entityTerm in entityTerms)
{
term.EntityName = entityTerm;
// x => x.Property == "Value" || x.AnotherProperty == "Value"
subExpression = Expression.OrElse(subExpression, GetComparisonExpression(term, parameterExpression));
}
}
// x => x.Property == "Value" && x.AnotherProperty == "Value"
finalExpression = Expression.AndAlso(finalExpression, hasMultipleTerms ? subExpression : GetComparisonExpression(term, parameterExpression));
}
// x => x.Property == "Value" && (x.AnotherProperty == "Value" || x.SomeAnotherProperty == "Value")
var lambdaExpression = ExpressionHelper.GetLambda<T, bool>(parameterExpression, finalExpression);
// How to do this conversion??
Expression<Func<T,bool>> returnValue = ..??;
return returnValue;
}
I'm trying to apply the result of above method to get the query as shown below:
public static IQueryable<T> GetQuery(IQueryable<T> inputQuery, ISpecification<T> specification)
{
var query = inputQuery;
// modify the IQueryable using the specification's criteria expression
if (specification.Criteria != null)
{
query = query.Where(specification.Criteria);
}
...
return query;
}
So that my final query will look like,
query = query.Where(x => x.Property == "Value" && (x.AnotherProperty == "Value" || x.SomeAnotherProperty == "Value"))
Edit-1:
Adding the ExpressionHelper.GetLambda
method as requested by @Ivan Stoev
public static class ExpressionHelper
{
public static LambdaExpression GetLambda<TSource, TDest>(ParameterExpression obj, Expression arg)
{
return GetLambda(typeof(TSource), typeof(TDest), obj, arg);
}
public static LambdaExpression GetLambda(Type source, Type dest, ParameterExpression obj, Expression arg)
{
var lambdaBuilder = GetLambdaFuncBuilder(source, dest);
return (LambdaExpression)lambdaBuilder.Invoke(null, new object[] { arg, new[] { obj } });
}
private static MethodInfo GetLambdaFuncBuilder(Type source, Type dest)
{
var predicateType = typeof(Func<,>).MakeGenericType(source, dest);
return LambdaMethod.MakeGenericMethod(predicateType);
}
}
Am I missing something very basic or doing anything wrong? Please assist.
Upvotes: 1
Views: 2788
Reputation: 205539
The ExpressionHelper.GetLambda<T, bool>
method used to obtain the lambda expression hides its actual type, which is the desired Expression<Func<T, bool>>
, so all you need is to use a cast operator:
return (Expression<Func<T, bool>>)lambdaExpression;
Or better, either change the result type of ExpressionHelper.GetLambda<TSource, TDest>
to Expression<Func<TSource, TDest>>
, or don't use that helper method - when you know the generic type arguments at compile time, simply use one if the generic Expression.Lambda methods (ExpressionHelper.GetLambda<TSource, TDest>
seems to be the equivalent of Expression.Lambda<Func<TSource, TDest>>
), e.g.
var lambdaExpression = Expression.Lambda<Func<T, bool>>(parameterExpression, finalExpression);
Upvotes: 1